Threatened & hidden: perceived job insecurity, facades of conformity and burnout - Tumelo, Tshepo Naomi (My University, 2022)
Background: The purpose of the study was to examine the relationship between perceived job insecurity and burnout (emotional exhaustion and disengagement) and facades of conformity (FOC) as a mediating variable. Methods: The study used a cross-sectional design. The sample comprised of 139 majority Southern African participants. This included 94 females (67.6%) and 45 males (45%) with a mean age of 31 years. In addition, the most represented age was 27 years (19.4%). Perceived job insecurity was measured using the Job Insecurity Inventory (JII); burnout was measured using the Oldenburg Burnout Inventory (OLBI) and facades of conformity was measured using the facades of conformity scale. In addition, all three instruments are self-report measures. Results: The sample presented with moderate levels of perceived job insecurity and FOC; and presented with moderate to high levels of burnout, emotional exhaustion, and disengagement. A positive moderate relationship was found between all the variables in the study therefore, the main effects were confirmed. It was found that FOC mediates the relationship between perceived job insecurity and burnout (estimate = .21, 95% CI [ .12, .32]); the relationship between perceived job insecurity and emotional exhaustion (estimate = .08, 95% CI [ .04, .14]); and the relationship between perceived job insecurity and disengagement (estimate = .13, 95% CI [ .07, .19]). In addition, it was found that the mediating effect of FOC is robust and remained significant after controlling for the effects of gender and age. Furthermore, it was found that disruption experienced because of the COVID-19 pandemic correlated positively with perceived job insecurity, FOC, burnout, emotional exhaustion, and disengagement. Additionally, types of COVID-19 pandemic disruptors predicted the experience of perceived job insecurity, burnout, and disengagement. In contrast, types of COVID-19 disruptors did not predict the experience of facades of conformity and emotional exhaustion. Conclusion: Organisational leaders are encouraged to facilitate an organisational culture that encourages authentic expression and celebrates individuality consequently, increasing organisation effectiveness. In addition, organisations are encouraged to focus on developing interventions that aim to reduce the experience of burnout. Furthermore, future research is encouraged to examine further, ideas around authentic expression and supressed identities at work.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2022